MATEC Web of Conferences - Shipilov; Eremeev; Balzovsky; Yurchenko Specialist in the field of electronics Associate Professor of Tomsk Polytechnic University, Candidate of medical sciences (2018)
In this paper, a method for detecting and mapping inhomogeneities in biological tissues using the radio-wave tomosynthesis method is presented. The proposed method of radio-wave tomosynthesis allows us to calculate the three-dimensional distribution of the permittivity of the space under study and, thereby, to detect tissue inhomogeneities and to determine their location and size. Due to their harmlessness for humans, these methods are suitable for dynamic observation of changes in the size of formation, in contrast to x-ray methods, for which regular doses of ionizing radiation are contraindicated. Therefore, the development of non-invasive methods for the search for inhomogeneities in biological media based on radio-wave sounding, which makes it possible to identify pathological formations, is now very relevant.